2017
DOI: 10.12968/live.2017.22.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Grassland management and helminth control on cattle farms

Abstract: Farmers manage their pastures and grazing animals primarily to ensure that swards provide adequate, quality nutrients to support animal performance, but it is also possible to provide useful levels of parasite control without compromising production. On cattle only farms the easiest options for the control of parasitic gastroenteritis in young cattle revolve around the avoidance of high risk pastures from July onwards. On many farms, silage/hay aftermaths that have not been grazed by cattle for 12 months or mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The presence of nurse cows among calves i.e. the concurrent grazing of susceptible young and resistant adult animals is supposed to reduce nematode infection of the former through a cleaning effect by adult animals, which ingest infective larvae while excreting few eggs in their faeces as demonstrated in beef cattle (Jäger et al, 2005;Thatcher, 2012;Forbes, 2016). However, when comparing several groups of grazing cow-calf pairs during two grazing seasons, Agneessens et al (1997) showed that the level of faecal egg counts in cows at turnout could be responsible for higher GIN infection in calves in autumn.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of nurse cows among calves i.e. the concurrent grazing of susceptible young and resistant adult animals is supposed to reduce nematode infection of the former through a cleaning effect by adult animals, which ingest infective larvae while excreting few eggs in their faeces as demonstrated in beef cattle (Jäger et al, 2005;Thatcher, 2012;Forbes, 2016). However, when comparing several groups of grazing cow-calf pairs during two grazing seasons, Agneessens et al (1997) showed that the level of faecal egg counts in cows at turnout could be responsible for higher GIN infection in calves in autumn.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that 'dose-and-move' can be effective in the control of lungworm (Eysker et al, 1996;Eysker et al, 1997), though adequate control of husk was not achieved on several farms in a larger scale study (Eysker et al, 1997). Mitigation of potential increased risks of selection for anthelmintic resistance through this practice have been addressed elsewhere (Forbes, 2017), though this aspect is of more relevance to PGE than PB.…”
Section: Dose-and-movementioning
confidence: 99%
“…Grazing with adult cows is also an option, but the risk of contamination of calf paddocks with infective larvae of D. viviparus (and Ostertagia ostertagi) is quite high. Moving FGS calves onto recently cut silage fields can provide relatively clean grazing and anthelmintic treatment at this time may be justified to help control PB (Eysker et al, 1996;Forbes, 2017).…”
Section: Spring-calving Dairy Herdsmentioning
confidence: 99%